PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR EKONOMI KELAS X DI SMA WISUDA PONTIANAK - Rahmah, Dewi; Ulfah, Maria; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research was to find out how much influence motivation to learn towards students’ learning outcomes on economic subjects in  X  class at SMA Wisuda Pontianak. The method used in this research was descriptiove in the form of a correlative study. The tools of data collection were questionnaire and documentation. This research had all of the 41 students of X class at SMA Wisuda Pontianak  as its population . In collecting the data, the researcher used indirect communication and documentary study technique. The tools of data collection used were questionnaire and docummentation. The technique of data analysis was descriptive and simple regression analysis. Based on the result from the t test that had been done, it hadobtained t value > t tablr (15,649> 2,023) therefore, Ho was rejected and Ha was accepted so that it could be conluded that motivation to learn  affected stundents’  learning outcomes on economic subjects in  X  class at SMA Wisuda Pontianak. The result of coefficient of determination was 0,863 which meant the contribution of the effect between motivation to learn toward student learning outcomes had 86,3% meanwhile the rest was 13,7% which was affected by another factor that was not included in this research. Keyword: Learning Outcomes, Students' Motivation to Learn